Landslides Hazard Assessment Using Soil Physics Approaches as a Determinant Factor on Agricultural Land in Hilly Area - Mujiyo, Mujiyo; Tiara Meti Pratingkas; Ongko Cahyono; Dwi Priyo Ariyanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Landslides are natural disasters that most often occur in hilly areas, one of which is in the Manyaran District, and are caused by land use, slope, and rainfall. This study aimed to assess the level of landslides on several slopes and determine the soil characteristics that most determine the level of landslide vulnerability to formulate an appropriate strategy for hilly land management. The sampling points used land map units (LMU) overlaid on thematic maps (land use, soil type, and slope), and were divided into 22 LMUs with three repeats for each LMU. The landslide level was calculated using a cumulative weight score. It was grouped based on the interval formula and modifications to the addition of permeability and soil texture parameters, while the determinants were analyzed using ANOVA and Pearson’s correlation. The results showed that the area was not very low (133.2 ha), low (1,015.33 ha), moderate (1,205.46 ha), high (3,248.48 ha), or very high(734.1 ha). The highest landslide hazard was on steep land (25–45%), and the determining factors were permeability and texture. The steeper the slope and the higher the permeability and soil texture values, the higher the landslide. The recommended landslide mitigation strategies are terracing and minimum tillage on agricultural land. Research on the level of landslides and information on determinant soil characteristics helps stakeholders formulate policies and manage agricultural land on hilly agricultural land.